Domino ring-opening–ring-closing enyne metathesis vs enyne metathesis of norbornene derivatives with alkynyl side chains. Construction of condensed polycarbocycles - Datta, Ritabrata; Ghosh, Subrata (Beilstein Journal of Organic Chemistry, 2018)
The metathesis of norbornene derivatives with alkynyl side-chain with Grubbs’ ruthenium alkylidine as catalyst has been investigated with the objective of constructing condensed polycyclic structures. This investigation demonstrated that the generally observed domino reaction course involving a ring-opening metathesis of the norbornene unit and a ring-closing enyne metathesis is influenced to a great extent by the nature of the functional group and the substrate structure and may follow a different reaction course than what is usually observed. In cases where ROM–RCEYM occurred, the resulting 1,3-diene reacts in situ with the dienophile to provide condensed tetracyclic systems.
Keywords: Diels–Alder reaction; domino process; enyne metathesis; natural products; polycarbocycles

(untitled) - Arjona, O.; Csáky, A. G.; Plumet, J. (Eur. J. Org. Chem., 2003)

(untitled) - Holub, N.; Blechert, S. (Chem. – Asian J., 2007)

(untitled) - Bose, S.; Ghosh, S. (Proc. Indian Natl. Sci. Acad., 2014)

(untitled) - Kotha, S.; Meshram, M.; Khedkar, P.; Banerjee, S.; Deodhar, D. (Beilstein J. Org. Chem., 2015)

(untitled) - Stille, J. R.; Santarsiero, B. D.; Grubbs, R. H. (J. Org. Chem., 1990)

(untitled) - Zuercher, W. J.; Hashimoto, M.; Grubbs, R. H. (J. Am. Chem. Soc., 1996)

(untitled) - Stragies, R.; Blechert, S. (Synlett, 1998)

(untitled) - Arjona, O.; Csákÿ, A. G.; Murcia, M. C.; Plumet, J. (Tetrahedron Lett., 2000)

(untitled) - Weatherhead, G. S.; Ford, J. G.; Alexanian, E. J.; Schrock, R. R.; Hoveyda, A. H. (J. Am. Chem. Soc., 2000)

(untitled) - Arjona, O.; Csákÿ, A. G.; Medel, R.; Plumet, J. (J. Org. Chem., 2002)

(untitled) - Sakurai, H.; Daiko, T.; Hirao, T. (Science, 2003)

(untitled) - Arjona, O.; Csákÿ, A. G.; León, V.; Medel, R.; Plumet, J. (Tetrahedron Lett., 2004)

(untitled) - Holtsclaw, J.; Koreeda, M. (Org. Lett., 2004)

(untitled) - Funel, J.-A.; Prunet, J. (Synlett, 2005)

(untitled) - Chandler, C. L.; Phillips, A. J. (Org. Lett., 2005)

(untitled) - Maechling, S.; Norman, S. E.; Mckendrick, J. E.; Basra, S.; Köppner, K.; Blechert, S. (Tetrahedron Lett., 2006)

(untitled) - Hart, A. C.; Phillips, A. J. (J. Am. Chem. Soc., 2006)

(untitled) - Phillips, A. J.; Hart, A. C.; Henderson, J. A. (Tetrahedron Lett., 2006)

(untitled) - Calvet, G.; Blanchard, N.; Kouklovsky, C. (Org. Lett., 2007)

(untitled) - Henderson, J. A.; Phillips, A. J. (Angew. Chem., Int. Ed., 2008)

(untitled) - Nguyen, N. N. M.; Leclère, M.; Stogaitis, N.; Fallis, A. G. (Org. Lett., 2010)

(untitled) - Lam, J. K.; Pham, H. V.; Houk, K. N.; Vanderwal, C. D. (J. Am. Chem. Soc., 2013)

(untitled) - Malik, C. K.; Ghosh, S. (Org. Lett., 2007)

(untitled) - Maity, S.; Ghosh, S. (Tetrahedron Lett., 2008)

(untitled) - Mondal, S.; Malik, C. K.; Ghosh, S. (Tetrahedron Lett., 2008)

(untitled) - Malik, C. K.; Yadav, R. N.; Drew, M. G. B.; Ghosh, S. (J. Org. Chem., 2009)

(untitled) - Malik, C. K.; Hossain, M. F.; Ghosh, S. (Tetrahedron Lett., 2009)

(untitled) - Mondal, S.; Yadav, R. N.; Ghosh, S. (Tetrahedron Lett., 2009)

(untitled) - Maity, S.; Ghosh, S. (Tetrahedron, 2009)

(untitled) - Matcha, K.; Maity, S.; Malik, C. K.; Ghosh, S. (Tetrahedron Lett., 2010)

(untitled) - Yadav, R. N.; Mondal, S.; Ghosh, S. (Tetrahedron Lett., 2011)

(untitled) - Bose, S.; Ghosh, M.; Ghosh, S. (J. Org. Chem., 2012)

(untitled) - Datta, R.; Bose, S.; Viththlbhai, P. B.; Ghosh, S. (Tetrahedron Lett., 2014)

(untitled) - Villar, H.; Frings, M.; Bolm, C. (Chem. Soc. Rev., 2007)

(untitled) - Diver, S. T.; Giessert, A. J. (Chem. Rev., 2004)

(untitled) - Mori, M. (Adv. Synth. Catal., 2007)

(untitled) - Mori, M. (Materials, 2010)

(untitled) - Banti, D.; North, M. (Adv. Synth. Catal., 2002)

(untitled) - Banti, D.; Groaz, E.; North, M. (Tetrahedron, 2004)

(untitled) - Groaz, E.; Banti, D.; North, M. (Eur. J. Org. Chem., 2007)

(untitled) - Kotha, S.; Ravikumar, O. (Tetrahedron Lett., 2014)

(untitled) - Kotha, S.; Ravikumar, O. (Eur. J. Org. Chem., 2014)

(untitled) - Spandl, R. J.; Rudyk, H.; Spring, D. R. (Chem. Commun., 2008)

(untitled) - Breitler, S.; Han, Y.; Corey, E. J. (Org. Lett., 2017)

(untitled) - Wright, J.; Drtina, G. J.; Roberts, R. A.; Paquette, L. A. (J. Am. Chem. Soc., 1988)

(untitled) - Wender, P. A.; Singh, S. K. (Tetrahedron Lett., 1990)

(untitled) - Hudlicky, T.; Fleming, A.; Radesca, L. (J. Am. Chem. Soc., 1989)

(untitled) - Datta, R.; Ghosh, S. (J. Org. Chem., 2017)